The Testing of Existence Wagner's Law in Papua Province - Muhammad Fajar; Yuyun Guna Winarti (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2021)
The Law of Wagner is supposedly not universally applicable. There are debates about the truth of this law. Based on this phenomenon, the purpose of this study is to examine the existence of Wagner's Law in the economy of Papua Province. Data used in this research are GRDP (Gross Regional Domestic Product) at the constant price (Real GRDP) and government expenditure at the constant price (Real GOV) in the form of natural logarithms (the base year 2000) from all municipalities in Papua Province from 2000 to 2013. Data source comes from Badan Pusat Statistik-Statistics Indonesia. The method used in this research is The Kao Cointegration Test and The Granger Causality Test. These methods indicate the possibility of short-term and long-term effects across economic variables. The result of this study concludes that there is a significant relationship between government expenditure and Gross Regional Domestic Product (GRDP). This result means that Wagner’s Law is not proven in the Papuan economy. This is supported by a causality test which shows government expenditure is granger cause of the real GDP, but not vice versa. However, the two variables are cointegrating.